Patient profile of uninsured patients at a private emergency department - Dippenaar (Forurie), Nicole (My University, 2018)
Background The aim of this study is to determine the patient profile of uninsured patients presenting to a private emergency department over a 3-month period. The study also looks at the time these patients spend in the private emergency department as well as reasons for delay in transfer when present. The study aims to assist the private emergency department in making financial and administrative plans for anticipated numbers of uninsured patients presenting to the unit in the future. Methods The study is a retrospective, cross-sectional study, reviewing patient data of uninsured patients presenting to a private emergency department in Tshwane over an allocated period from 01 September 2014 to 30 November 2014. The study population is any uninsured patient presenting to the private emergency department over the 3 month period and was identified by searching the existing patient register in the unit. The data collected includes age, gender, priority of the patients according to triage protocol, provisional diagnoses, outcome, time that a patient spends in the unit before transfer, admission or discharge and reasons for delay in transfer if experienced. The number of patients over the entire period as well as over each individual month was recorded and analysed. Results The total number of uninsured patient visits to the private ED over the 3-month period was 503 which included follow up visits. The total number of ED visits for insured and uninsured patients was 6505. Uninsured patients accounted for 7.7% of the total number of visits to the ED. There was a total of 427 uninsured patients (excluding follow up visits) seen in the private ED over the 3-month period. This is the study sample number. There were on average more patients seen over the weekend and the majority iv of all the uninsured patients were non-urgent cases. Seventy nine percent were discharged, 12% were transferred to a government facility, 7% were admitted to the private facility and 2% refused hospital treatment. There were 20 delays in transfer to government facilities identified. Conclusions The study provides insight into the patient profile and number of uninsured patients presenting to a private emergency department in South Africa over a 3-month period. This data can assist the emergency department in planning and managing these patients who often present a challenge to the physician due to delays when transferring the ill patients to government facilities.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment for the degree of Master of Science in Medicine (Emergency Medicine)
Keywords: Emergency Service, Hospital; Medically Uninsured